Quantum confinement effect and photoenhancement of photoluminescence of PbS and PbS/MnS quantum dots - Zaini, Muhammad Safwan; Josephine Ying, Chyi Liew; Alang Ahmad, Shahrul Ainliah; Mohmad, Abdul Rahman; Ahmad Kamarudin, Mazliana (Multidisciplinary Digital Publishing Institute, 2020)
The quantum confinement effect and photoenhancement of photoluminescence (PL) of lead sulphide (PbS) quantum dots (QDs) and lead sulphide/manganese sulphide (PbS/MnS) core shell QDs capped with thiol ligands in aqueous solution were investigated. From PL results, the presence of MnS shells gives a strong confinement effect which translates to higher emission energy in PbS/MnS core shell QDs. Increasing MnS shell thickness from 0.3 to 1.5 monolayers (ML) causes a blueshift of PL peak energies as the charge carriers concentrated in the PbS core region. Enhancement of the PL intensity of colloidal PbS and PbS/MnS core shell QDs has been observed when the samples are illuminated above the band gap energy, under continuous irradiation for 40 min. Luminescence from PbS QDs and PbS/MnS core shell QDs can be strongly influenced by the interaction of water molecules and oxygen present in aqueous solution adsorbed on the QD surface. However, PbS/MnS core shell QDs with a shell thickness of 1.5 ML did not show a PL peak energy stability as it was redshifted after 25 min, probably due to wider size distribution of the QDs.